Habitat Anaphalis spp. in Tourism Area in Bromo Tengger Semeru National Park, East Java - Filza Yulina Ade; Luchman Hakim; Estri Laras Arumingtyas; Rodiyati Azrianingsih (Jurnal Pembangunan dan Alam Lestari)
The conservation of Anaphalis in moutian area in Bromo Tengger Semeru National park require basic understanding of habitat profiles. The aims of the research is to describes the habitat profile of Anaphalis spp population in mountain area in Bromo Tengger Semeru National Park. This research confirm that three Anaphalis were identified, namely Anaphalis javanica, Anaphalis viscida and Anaphalis longifolia. These species found at Penanjakan, Mt. Batok, and Ranu Kumbolo. The habitat of Anaphalis in study area were influenced by volcanic activities. Anaphalis grows in silty loam, loam, sandy-silt loam and sandy loam soils. Â Anaphalis grows in high competition with weeds and exotic plant species. Exotic-invasise species such as Agrostis sp., Imperata cylindrical, Pteridium sp., Alchemilla sp. Eupatorium sp. and Leucaena sp. plays an important role as a competitor among Anaphalis spp population in wild area. The conservation of Anaphalis in natural habitat require significant action to minimize invasive plant species in Anaphalisâ€™s habitat.